Insider-trading, discretionary accruals and information asymmetry - Sabur Mollah (The British Accounting Review)
Using US data for the period from 2004 to 2012 and alternative discretionary accruals measures, we examine whether insiders manipulate earnings in an asymmetric information environment to profit from their informed trades, and whether the intervening information environment influences the relationship between earnings management and insider trading. We show that insider trading dominated by sell trades has a positive association with discretionary accruals. The incremental effect of information asymmetry as well as the interaction with insider trading is also prevalent in this relation, confirming the moderating effect of asymmetric information. Further, we show that the active involvement of some key insiders in high discretionary accruals is for personal benefit more in growth firms than in value firms. Our results also suggest that earnings management allows for insiders’ opportunistic, rather than routine, buy and sell trades. Our findings highlight that regulators should oversee and scrutinise both insider trading and earnings management to mitigate the risk of the opportunistic behaviour of insiders to avoid future corporate scandals.Keywords: insider trading, discretionary